Relationships between tissue levels of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), mRNAs and toxicity in the developing male Wistar(Han) rat - Bell, David Robert; Clode, Sally; Fan, MingQi; Fernandes, Alwyn; Foster, Paul M D; Jiang, tao; Loizou, George; MacNicoll, Alan; Miller, Brian G; Rose, Martin; Tran, Lang; White, Shaun (Oxford University Press, 2007)
We compared the effects of a single acute dose, or chronic fetal exposure, to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on the male reproductive system of the Wistar(Han) rat. Tissue samples were taken from dams on GD16 and GD21, and from offspring on PND70 and 120. Steady state concentration of TCDD was demonstrated in the chronic study: body burdens were comparable in both studies. Fetal TCDD concentrations were comparable after acute and chronic exposure, and demonstrate more potent toxicity after chronic versus acute dosing. In maternal liver, cytochrome P450 (CYP)1A1 and CYP1A2 RNA were induced. In fetus, there was induction of both CYP1A1 and CYP1A2 RNA at medium and high doses, but inadequate evidence for induction at low dose in either study. The low level induction of CYP1A1 RNA at low dose in fetus argues against AhR activation in fetus as a mechanism of toxicity of TCDD in causing delay in balanopreputial separation, and the greater induction of CYP1A1 RNA in PND70 offspring liver suggests that lactational transfer of TCDD is crucial to this toxicity. These data characterise the maternal and fetal disposition of TCDD, induction of CYP1A1 RNA as a measure of AhR activation, and suggest that lactational transfer of TCDD determines the difference in delay in balanopreputial separation between the two studies.